Antioxidant, Antimicrobial, Cytotoxic, and Protein Kinase Inhibition Potential in Aloe vera L. (28th July 2019) - Tariq, Huma; Zia, Muhammad; Ihsan-ul-Haq,; Muhammad, Syed Aun; Khan, Shujaat Ali; Fatima, Nighat; Mannan, Abdul; Abbasi, Arshad Mehmood; Zhang, Mingxing
Abstract : Aloe vera is a multifunctional plant that has gained acceptance as an excellent home remedy source in Asia and the world. The present study was intended to evaluate the phytochemical contents and in vitro antioxidant, antimicrobial, antileishmanial, and protein kinase inhibition activities in different fractions of A. vera leaf. Methanolic extract of A. vera leaves was fractionated using column chromatography and ten fractions (AV1-AV10) were obtained. Phenolics composition, antioxidant, antimicrobial, antileishmanial, and protein kinase inhibition activities were evaluated using standard protocols. Well-known compounds of A. vera were used for in silico study against enzymes involved in brine shrimp and antileishmanial and hyphae formation inhibition assay on the basis of results. Five fractions (AV3 to AV7) possess potential total phenolics and flavonoids contents along with significant biological activities. AV4 fraction exhibited the highest total phenolics content 332.4 ± 32.6 μ g GAE/mg and total antioxidant activity 150.4 ± 25.815 μ g AAE/mg determined by phosphomolybdenum complex assay. Fraction AV6 showed 95% antileishmanial effect as well as the lowest LD50 value of 0.5305 μ g/mL in brine shrimp lethality assay. The Protein Kinase inhibition potential in A. vera leaves was determined for the first time and three fractions AV1, AV6, and AV7 depicted activity with the highest zone of inhibition up to 21±0.5mm (AV7). Docking analysis showed that A. vera contains anthraquinones, anthrones, chromones, and polysaccharides responsible for synergistic cytotoxic, antileishmanial, antibacterial, and antioxidant potential of this plant. Therefore, with more studies, A. vera could probably have the potential to be used for drug development against leishmaniasis.